A Novel Algorithm for Removing Impulse Noise From Highly Corrupted Image - Khan, Aijaz Ur Rahman; Thakur, Kavita (Richtmann Publishing, 2012)
Various switching-based median filter have been proposed in the literature for restoration of extremelycorrupted images by impulsive noise (Salt and pepper noise). Progressive switching median filter (PSMF)and Boundary discriminative noise detection (BDND) median filter are some of these. It is well known thatstandard median filter(SMF) is not suitable for removing impulse noise from highly corrupted images. Thepoor efficiency of this filter is due to the fact that it is not able to discriminate the noisy pixel from noiselesspixel. The proposed method uses noise detection stage and then adaptive window shaped filtering stage forthe restoration of images contaminated by impulse noise. The performance of the proposed method isdemonstrated through computer simulation in comparison with the PSMF method and standard medianfilter.